Financial Literacy Analysis, Financial Management and Needs for Economic Conditions (Case Study of Kwala Sefragile Village Community, Langkat) - Maya Macia Sari; Eli Delvi Yanti; Rizco Rama Doni (Yayasan Multidimensi Kreatif, 2023)
This study aims to analyze the influence of Financial Literacy, Financial Management Patterns and Needs on Economic Conditions. The location of the study was conducted in Kwala Sefragile Village, Tanjung Pura District, Langkat Regency. The sample in this study was a community of business actors as many as 70 respondents. The analysis method used is multiple linear regression analysis. The results of the study show that Financial Literacy has a partial positive but not significant effect on the State of the Economy. Financial Management has a positive and significant effect on the State of the Economy. Needs have a positive and significant effect on the State of the Economy. While simultaneously Financial Literacy, Financial Management and Needs have a positive and significant effect on the State of the Economy. The contribution of the influence of Financial Literacy, Financial Management and Needs on Economic Conditions is 66.4%